Elimination of Pseudomonas aeruginosa through Efferocytosis upon Binding to Apoptotic Cells - Capasso, Dario Nicolás (2016)
For opportunistic pathogens such as Pseudomonas aeruginosa, the mucosal barrier represents a formidable challenge. Infections develop only in patients with altered epithelial barriers. Here, we showed that P. aeruginosa interacts with a polarized epithelium, adhering almost exclusively at sites of multi-cellular junctions. In these sites, numerous bacteria attach to an extruded apoptotic cell or apoptotic body. This dead cell tropism is independent of the type of cell death, as P. aeruginosa also binds to necrotic cells. We further showed that P. aeruginosa is internalized through efferocytosis, a process in which surrounding epithelial cells engulf and dispose of extruded apoptotic cells. Intracellularly, along with apoptotic cell debris, P. aeruginosa inhabits an efferocytic phagosome that acquires lysosomal features, and is finally killed. We propose that elimination of P. aeruginosa through efferocytosis is part of a host defense mechanism. Our findings could be relevant for the study of cystic fibrosis, which is characterized by an exacerbated number of apoptotic cells and ineffective efferocytosis.